Anti-allergic Activity of 70% Ethanol Extract of Strawberries in Ovalbumin Induced Male Mice - Siska; Diene Roufiani; Ema Dewanti (Tropical Biopharmaca Research Center, IPB University, 2020)
Anaphylaxis is the most common allergic reaction triggered by allergens such as insect poisons, food, and drugs through skin contact, injection, or inhalation. In vitro previous research showed that strawberries fruit have activity as antioxidant, anticancer, anti-inflammation, and anti-allergic. The research aimed to determine the antianaphylaxis strawberry fruit extract in mice (Balb/C strain) with ovalbumin-induced. Twenty-four Balb/C strain mice were divided into six groups (n=4). Group I and II as a normal and control group. Group III till VI as a treatment group was given cetirizine dose 0.042 mg/20 g BW and strawberry extract doses 0,68; 1,36; and 2,72 mg/20 g BW, respectively. This research showed that 70 % of ethanol extract of strawberries fruit have antiallergic activity in response to active cutaneous anaphylaxis. 70% ethanol extract of strawberries doses 2.72 mg/20 g BW had similar antiallergic activity compare with cetirizine. The conclusion of this study showed that strawberries fruit extract could be developed as an alternative medicine to anti-anaphylaxis or anti-allergic.